Identifying Logging Practices in Open Source Python Containerized Application Projects - Alves, Marco; Paula, Hugo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Despite the popularity of microservice architectures using container based virtualization, there are not many studies that describe how logging practices are being employed in this scenario. In this empirical study, we cloned 10,918 of the most stargazed GitHub Python repositories with a Docker/Kubernetes associated file. We were able to find 1,166 Python projects that used containers. A custom parser identified and saved log statements from Python source code. We discovered that certain licenses tend to have a higher log density; over 99% of projects use the built-in Python logging library; the repository age does not affect its log statements/LLOC ratio; logging verbosity levels debug and info are used almost twice as much as warning and error. We hope our study provides the community with useful data about this topic, possibly contributing to the improvement of techniques that stimulate its applications.